Intelligent Nanosystems for Energy, Information and Biological Technologies - Sone, Jun'ichi.; Tsuji, Shinji; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book gives a state-of-the-art view by recognized researchers of the nanotechnologies required for future integrated systems leading to innovations in energy, the environment, and biotechnologies. Nanostructures that would be difficult to form using the current semiconductor technology will be realized using a combination of bottom-up and top-down processes, including hybrid nanostructures made of inorganic and organic/biological materials. Bio-sensing, imaging, and cell or molecular manipulation are discussed in Chapters 2-7. The acquisition of basic knowledge on the cellular level will lead to curing serious diseases. Also, nanofabrication technologies, discussed in Chapters 8-15, will lead to next-generation solar cells, secondary batteries, and advanced electronic circuits using nanostructured materials, thus providing solutions for serious energy and environment issues. Prospective readers of this book include graduate students as well as researchers and engineers working in this field.
Evolution of Nanotechnology to Intelligent Nano-system -- Field-effect Transistors for Detection of Biomolecular Recognition -- Bio-imaging System with High Resolution and Sensitivity for Biological Science　and Medical Application -- Development of High Throughput Screening Device for Neurodegenerative Diseases -- Extended-nano-scale Fluidics and Applications to Bioanalysis -- Microfluidic Approach to Cell Handling and Measurement -- Digital Bioassay with Femtoliter Reactor Array -- Bio Templates and Their Application to Electronic Devices -- Fabrication of 3D Quantum Dot Array by Fusion of Bio-template and Neutral Beam Etching I: Basic Technologies -- Fabrication of 3D Quantum Dot Array by Fusion of Bio-template and Neutral Beam Etching II: Application to QD Solar Cells and Laser/LED -- Development of Novel Nano Systems for Electrochemical Devices by Hierarchizing Concentrated Polymer Brushes -- Metallo-supramolecular Polymers: Design, Function and Device Application -- Feasibility of Fabricating Large-area Inorganic Crystalline Semiconductor Devices -- Synthesis of Subnano-particles Using a Dendrimer Template -- Electrochemistry-based Smart Biodevices -- Spin Current Physics and Its Thermoelectric Application.
Keywords: Nanotechnology; Nanochemistry; Nanoscience; Neurosciences; Microtechnology; Microelectromechanical systems; Radiology; Nanotechnology; Nanochemistry; Nanophysics; Neuroscience; Microsystems and MEMS; Radiology